New Relations Involving an Extended Multiparameter Hurwitz-Lerch Zeta Function with Applications. (13th May 2014) - Srivastava, H. M.; Gaboury, Sébastien; Tremblay, Richard
Abstract : We derive several new expansion formulas involving an extended multiparameter Hurwitz-Lerch zeta function introduced and studied recently by Srivastava et al. (2011). These expansions are obtained by using some fractional calculus methods such as the generalized Leibniz rules, the Taylor-like expansions in terms of different functions, and the generalized chain rule. Several (known or new) special cases are also given.